TAFSIR AT-TANWIR MUHAMMADIYAH DALAM SOROTAN (Telaah Otoritas Hingga Intertekstualitas Tafsir) - ARIVAIE RAHMAN; SRI ERDAWATI (Fakultas Ushuluddin dan Humaniora UIN Antasari Banjarmasin, 2019)
This paper reviews Tafsir at-Tanwir (2015) written by the Tarjih dan Tajdid Pimpinan Pusat Muhammadiyah. This research focuses on behind the scenes writing Tafsir at-Tanwir. Besides, it also examines the idea of progressing Qur’anic interpretation, in the form of direction and importance of interpretation, systematic and technical interpretation, and sources of reference of interpretation. This type of research is library research by relying on Tafsir at-Tanwir as primary data and other literature as secondary sources. Content review using the descriptive-analysis method is supported by historical and hermeneutic approaches. Based on the analysis conducted in this study, several results were obtained: first, the authors of the interpretation are academics and activists of Muhammadiyah, they work at leading Islamic universities in Indonesia, it is very appropriate to call this interpretation as “academic interpretation”. This interpretation is not only written by men but also involves the role of women writers. The performance of the interpretations of each team of interpreters varies, some are individual and some are collective, at most interpret 29 verses and at least 1 verse. Secondly, the importance of writing Tafsir at-Tanwir is to mobilize the puritan ideology of Muhammadiyah. In addition, to create responsive interpretations, generate dynamics, and contain the ethos of Muhammadiyah, in the form of an ethos of worship, economic, social, and science. Writing interpretation is very systematic. As a progressive interpretation of the Qur’an, Tafsir at-Tanwir also dares to refer to Arabic and English references, but unfortunately, some still refer to translated books.